Analisis Kesiapan Prodi PGMI STIT Pringsewu Lampung dalam Pembelajaran Daring Menyikapi Dampak Pandemi virus Covid 19: indonesia - Apri Wahyudi; Marzuki, Idelia; Abdul Hamid; Evi Gusliana (LPPM STIT PRINGSEWU, 2021)
Abstract This study aims to determine the level of readiness for the application of e-learning in Department of Teachers Elemntary School and identify any factors that are still weak in the application of e-learning in the Department of Teachers Elemntary School. This research is a descriptive study with a quantitative approach. The research model in this study used a questionnaire instrument namely the ELR Aydin and Tasci models to measure the readiness of implementing e-learning. The variable in this study is the level of readiness for the application of e-learning as seen from several factors, namely (1) technological factors (2) innovation factors (3) human factors (4) self-development factors The level of readiness in this study is the level or circumstances achieved by the Department of Mathematics Education in the application of e-learning. Data analysis using ELR Aydin and Tasci models, the scores used in the assessment sheet are 5, 4, 3, 2, and 1 for each question to calculate the total score, and then the final average is calculated. The results obtained, the level of readiness for the application of e-learning in the Department of Mathematics Education obtained an average score of 4.29, which means ready in implementing e-learning but requires a slight increase. The level of readiness on the technology factor obtains an average score of 43 which means it is ready in implementing e-learning The level of readiness on the innovation factor obtains an average score of 4.24 which means it is ready in implementing e-learning but requires a slight increase. The level of readiness on the human factor obtains an average score of 429 which means it is ready in implementing e-learning but requires a slight increase. The level of readiness on the factor of self-development obtained an average score of 4.27 which means it is ready in implementing e-learning but requires a slight increase. Keywords: Readiness, E-Learning, Covid-19 Abstrak Penelitian ini bertujuan untuk mengetahui tingkat kesiapan penerapan e-learning di Jurusan Keguruan SD dan mengidentifikasi faktor-faktor apa saja yang masih lemah dalam penerapan e-learning di Jurusan Keguruan SD. Penelitian ini merupakan penelitian deskriptif dengan pendekatan kuantitatif. Model penelitian dalam penelitian ini menggunakan instrumen angket yaitu model ELR Aydin dan Tasci untuk mengukur kesiapan penerapan e-learning. Variabel dalam penelitian ini adalah tingkat kesiapan penerapan e-learning dilihat dari beberapa faktor yaitu (1) faktor teknologi (2) faktor inovasi (3) faktor manusia (4) faktor pengembangan diri Tingkat kesiapan dalam penelitian ini adalah tingkat atau keadaan yang dicapai oleh Departemen Pendidikan Matematika dalam penerapan e-learning. Analisis data menggunakan model ELR Aydin dan Tasci, skor yang digunakan pada lembar penilaian adalah 5, 4, 3, 2, dan 1 untuk setiap pertanyaan untuk menghitung skor total, kemudian dihitung rata-rata akhir. Hasil yang diperoleh, tingkat kesiapan penerapan e-learning di Jurusan Pendidikan Matematika diperoleh skor rata-rata 4,29 yang artinya siap dalam menerapkan e-learning namun membutuhkan sedikit peningkatan. Tingkat kesiapan pada faktor teknologi memperoleh skor rata-rata 43 yang berarti siap dalam mengimplementasikan e-learning Tingkat kesiapan pada faktor inovasi memperoleh skor rata-rata 4,24 yang berarti siap dalam mengimplementasikan e-learning tetapi membutuhkan sedikit peningkatan. Tingkat kesiapan pada faktor manusia memperoleh skor rata-rata 429 yang berarti sudah siap dalam menerapkan e-learning namun memerlukan sedikit peningkatan. Tingkat kesiapan pada faktor pengembangan diri diperoleh skor rata-rata 4,27 yang berarti sudah siap dalam menerapkan e-learning namun memerlukan sedikit peningkatan. Kata kunci: Kesiapan, E-Learning, Covid-19